A proposed instructional module on the concept "change" for second year high school - Manuel, Diana Samsuya 1950- (1977)
The purpose of the study was to propose a module on the concept "change." A module is a self-contained instructional unit which students can study at their own rate with little help from the teacher. Also included in the module is a note for the teachers and students containing instructions on how to go about the module. One approach to effective individualized instruction is the use of module. It enables the students to have freedom in selecting learning activities that will help him reach his career goal. Thus resulting in the learner becoming a more self-reliant and more resourceful individual.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices; Individualized instruction -- Philippines